PENGUNGKAPAN EMISI KARBON DAN ENVIRONMENTAL PERFORMANCE TERHADAP NILAI PERUSAHAAN - Pangestika, Friska Oktaviana Widya; Astuti, Christina Dwi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This research was conducted to test whether there is a positive influence from Disclosure of Carbon Emissions and Environmental Performance on Company Value with Company Size as a control variable. This test uses 234 samples obtained from 78 Consumer Non-Cyclical companies with a time span of 3 years, namely 2021 to 2023. Based on the results of research and hypothesis testing that has been carried out by researchers, the conclusion is as follows: Carbon Emission Disclosure has an effect positive effect on company value, and environmental performance has a positive effect on company value. Keywords: Carbon Emissions, Environmental Performance, Company.